Morphological and Immunohistochemical Description of a Splenic Haemangioma in a Captive European Wolf (Canis lupus lupus) and a Review of the Current Literature - Josep Maria Monné Rodríguez; Federico Morandi; Paolo Cavicchio; Alessandro Poli; Ranieri Verin (Veterinary Sciences, 2020)
Neoplastic diseases are rarely described in wild carnivores; only a few reports have been published on this topic. Here, we describe the histological and immunohistochemical features of a haemangioma in the spleen of a grey wolf (Canis lupus lupus) and we compare the results with the dog (Canis lupus familiaris). Additionally, we list the different publications found in the literature with neoplastic lesions in wolves. Our results show similar immunohistochemical features to dogs, in which neoplastic cells express Vimentin, von Willebrand factor, alpha smooth muscle actin antibody, vascular endothelial growth factor C and low vascular endothelial growth factor receptor 3. Toluidine blue special stain shows moderated increased numbers of mast cells infiltrating the tumor, a feature observed in benign vascular tumors in domestic dogs, but not in the malignant counterparts. To our knowledge, this is the first article describing the gross, histological and immunohistochemical features of a splenic haemangioma in a wolf.